Męskość i homoseksualizm w popkulturze - tożsamość gejów w wybranych współczesnych filach i serialach. Zarys problematyki - Drabina, Aleksandra (Institute of Sociology, University of Wrocław, 2015)
The priority of this publication is showing the role of American popular films and tv series in creating symbolic narrations about gay men identity and showing characteristic components of their creations. The particular content is a compilation fragments of research studies, that were part of my two graduation projects. The article is a depiction of searching by semiology analysis signs and meanings in chosen gay men images from movies and tvseries. The analysis register their common symbolic structures and show the evolution indirections of contemporary explorations of homosexual masculinity in popular culture.
Keywords: gay men; homosexuality; masculinity; pop culture; semiology